"FlashMap" - A Semi-Automatic Tool for Rapid and Accurate Spatial Analysis of Marker Expression in the Subventricular Zone. Issue 1 (December 2018) - Zweifel, Stefan; Buquet, Julie; Caruso, Lorenzo; Rousseau, David; Raineteau, Olivier
Abstract The subventricular zone (SVZ) is a region of ongoing postnatal germinal activity that shows complex spatial heterogeneity. For instance, different SVZ microdomains contain neural stem cells that express distinct transcription factors and generate different glial and neuronal progenies. These unique characteristics call for the development of new methods to integrate a spatial dimension to histological analyses performed in this germinal region. We developed "FlashMap", a semi-automatic software that allows the segmentation and rapid measurement of optical densities throughout the full SVZ coordinates. "FlashMap" generates easily readable two-dimensional heatmaps that can be superimposed onto three-dimensional reconstructions of the ventricular system for optimal spatial exploration. Accurate heatmaps can be obtained, even following serial section subsampling thereby reducing the amount of tissue and time required for histological analysis. We first illustrate the potential of "FlashMap" by spatially exploring the correlation of SVZ thickness and cellular density with germinal activity throughout its rostro-caudal coordinates. We then used "FlashMap" to analyse the spatial expression of the transcription factors Dlx2, Tbr2 and Hopx as well as of the immature neuronal marker Dcx, to demonstrate the suitability of this approach to explore the regional production of cells of distinct lineages by defined SVZ microdomains.